Disaster Manual Emergency, Evacuation, Recovery - Koplowitz, Brad.; Oklahoma State Dept. of Libraries, Oklahoma City. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This manual outlines the responsibilities of the director of the Oklahoma Department of Libraries in the event of a disaster as well as the functions of the emergency recovery team (ERT) in the coordination of recovery, and emergency action steps to be taken. The evacuation and emergency plan provided for the Allen Wright Memorial Library Building includes emergency telephone numbers, a bomb threat checklist, library floor plans illustrating exit routes, and emergency operation procedures. The appended discussion of salvage procedures for treatment of water-damaged paper and microfilm includes a safety checklist, instructions for using a fire extinguisher, a material priority list, a material damage report form, and a list of emergency supplies and equipment together with suppliers. (RBF)
ERIC Note: Best available copy.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Emergency Programs; Guidelines; Library Facilities; Library Materials; Library Personnel; Preservation; State Libraries; Guides, General